Incidence and Risk Factors of Coagulation Profile Derangement After Liver Surgery: Implications for the Use of Epidural Analgesia—A Retrospective Cohort Study. (April 2018) - Jacquenod, Pierre; Wallon, Grégoire; Gazon, Mathieu; Darnis, Benjamin; Pradat, Pierre; Virlogeux, Victor; Farges, Olivier; Aubrun, Frédéric
Abstract : BACKGROUND: Hepatic surgery is a major abdominal surgery. Epidural analgesia may decrease the incidence of postoperative morbidities. Hemostatic disorders frequently occur after hepatic resection. Insertion or withdrawal (whether accidental or not) of an epidural catheter during coagulopathic state may cause an epidural hematoma. The aim of the study is to determine the incidence of coagulopathy after hepatectomy, interfering with epidural catheter removal, and to identify the risk factors related to coagulopathy. METHODS: We performed a retrospective review of a prospective, multicenter, observational database including patients over 18 years old with a history of liver resection. Main collected data were the following: age, preexisting cirrhosis, Child-Pugh class, preoperative and postoperative coagulation profiles, extent of liver resection, blood loss, blood products transfused during surgery. International normalized ratio (INR) ≥1.5 and/or platelet count <80, 000/mm 3 defined coagulopathy according to the neuraxial anesthesia guidelines. A logistic regression analysis was performed to assess the association between selected factors and a coagulopathic state after hepatic resection. RESULTS: One thousand three hundred seventy-one patients were assessed. Seven hundred fifty-nine patients had data available about postoperative coagulopathy, which was observed in 53.5% [95% confidence interval, 50.0–57.1]. Maximum derangement in INR occurred on the first postoperative day, and platelet count reached a trough peak on postoperative days 2 and 3. In the multivariable analysis, preexisting hepatic cirrhosis (odds ratio [OR] = 2.49 [1.38–4.51]; P = .003), preoperative INR ≥1.3 (OR = 2.39 [1.10–5.17]; P = .027), preoperative platelet count <150 G/L (OR = 3.03 [1.77–5.20]; P = .004), major hepatectomy (OR = 2.96 [2.07–4.23]; P < .001), and estimated intraoperative blood loss ≥1000 mL (OR = 1.85 [1.08–3.18]; P = .025) were associated with postoperative coagulopathy. CONCLUSIONS: Coagulopathy is frequent (53.5% [95% confidence interval, 50.0–57.1]) after liver resection. Epidural analgesia seems safe in patients undergoing minor hepatic resection without preexisting hepatic cirrhosis, showing a normal preoperative INR and platelet count.